In situ Evaluation of the Erosive Potential of Orange Juice Modified by Food Additives - Scaramucci, T.; Sobral, M.A.P.; Eckert, G.J.; Zero, D.T.; Hara, A.T. (Caries research, 2012)
The aim of this study was to evaluatethe erosive potential of orange juice modified with food-approved additives: 0.4 g/l of calcium (Ca) from calcium lactate pentahydrate, 0.2 g/l of linear sodium polyphosphate (LPP) or their combination (Ca+LPP) were added to a commercially available orange juice (negative control, C–). A commercially available calcium-modified orange juice (1.6 g/l of calcium) was the positive control (C+). These juices were tested using a short-term erosion in situmodel, consisting of a five-phase, single-blind crossover clinical trial involving 10 subjects. In each phase, subjects inserted custom-made palatal appliances containing 8 bovine enamel specimens in the mouth and performed erosive challenges for a total of 0 (control), 10, 20, and 30 min. Two specimens were randomly removed from the appliances after each challenge period. Enamel surface microhardness was measured before and after the clinical phase and the percentage of surface microhardness change (%SMC) was determined. Before the procedures, in each phase, the subjects performed a taste test, where the juice assigned to that phase was blindly compared to C–. Overall, C+ showed the lowest %SMC, being the least erosive solution (p < 0.05), followed by Ca+LPP and Ca, which did not differ from each other (p > 0.05). LPP and C– were the most erosive solutions (p < 0.05). Taste differences were higher for C+ (5/10 subjects) and Ca (4/10 subjects), but detectable in all groups, including C– (2/10 subjects). Calcium reduced the erosive potential of the orange juice, while no protection was observed for LPP.